2014
DOI: 10.5455/medarh.2014.68.279-281
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hydroxyethyl Starch 6% and Crystalloids for Preloading in Elective Caesarean Section Under Spinal Anesthesia

Abstract: Background:Although controversial, many studies have shown effectiveness of colloid loading as a substitute for crystalloids on reducing the incidence of hypotension in spinal anesthesia. This study was conducted to compare the effects of three intravenous fluid regimens on hemodynamic changes following spinal anesthesia in cesarean section. The regimens included 6% Hydroxyethylstarch 130/0.4 (HES) as a colloid and two crystalloids (lactated ringer’s solution and sodium chloride 0.9%).Material & Method:In a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
2
10
1
1
Order By: Relevance
“…Mean percentage of HR changes showed a significant difference between the intervention groups; the rate of changes was more in the crystalloid group than the colloid group. These findings were not consistent with those of Alimian et al, in which HR changes showed no significant difference between the two groups ( 17 ). Average injected ephedrine was significantly lower in the colloid solution group than the other group and this was not consistent with the results of Unlugenc et al, in which injected ephedrine showed no significant difference between the two intervention groups ( 18 ).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Mean percentage of HR changes showed a significant difference between the intervention groups; the rate of changes was more in the crystalloid group than the colloid group. These findings were not consistent with those of Alimian et al, in which HR changes showed no significant difference between the two groups ( 17 ). Average injected ephedrine was significantly lower in the colloid solution group than the other group and this was not consistent with the results of Unlugenc et al, in which injected ephedrine showed no significant difference between the two intervention groups ( 18 ).…”
Section: Discussioncontrasting
confidence: 97%
“…After estimating average Apgar at minutes one and five and according to the results, no significant difference was reported and it was consistent with the findings of Alimian et al, where the Apgar scores showed no significant difference between the two groups. The amounts of the total infused solution after spinal anesthesia were significantly different between the two intervention groups, where the colloid solution showed lower amount ( 17 ). This finding was not consistent with that of the study conducted by Unlugenc et al, where the average solution injected after spinal anesthesia did not show significant difference between the two groups ( 18 ).…”
Section: Discussionmentioning
confidence: 96%
“…We included 109 out of 1021 retrieved trials, which included 8561 women (Fig. and see also Supporting Information, Table S1) . Twelve interventions (eleven active treatments and one inactive control) to prevent intra‐operative hypotension were studied, with 30 direct comparisons (see also Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…In all newborn babies (except 8 babies in the control group and 10 babies in case group) at least had Apgar score[ 9 ] at 1 st min and Apgar score[ 10 ] at 5 th min which there was not significant difference in two groups ( P > 0.05). Babies who have lower Apgar score had not an Apgar score of <8 at 5 th min in two groups ( P > 0.05).…”
Section: Resultsmentioning
confidence: 92%
“…reported the prevalence of hypotension after spinal anesthesia in parturients is between 80% and 90%. [ 5 9 10 11 ] Dahlgren et al . by applying 1000 cc liquid 3% dextran immediately before spinal anesthesia for elective cesarean section compared to Ringer's lactate reported that the overall incidence of hypotension reduces from 85% to 66%, incidence of clear clinical hypotension reduces from 60% to 30% and Severe hypotension reduces from 23% to 3.6%.…”
Section: Discussionmentioning
confidence: 99%